Influence of ENSO on the Coastal Upwelling along Northwest Africa - Sthitapragya, Ray; Baranova-Parfenova, Elizaveta; Cabrera, Andrea A.; Guzmán, Diana; Proklova, Daria (Zenodo, 2024)
The El Niño Southern Oscillation (ENSO) is known to influence global atmospheric and oceanic conditions through teleconnection effects. Further, it is also known that teleconnection effects are highly sensitive to ENSO diversity (the variation in the location of the warm SST anomalies). In this analysis, we have analysed the teleconnection between ENSO and the North West African (NWA) coastal upwelling system. This upwelling system consists of two parts: the northern part of coastline is a permanent upwelling system (with cool coastal SST prevalent throughout the year) and the southern part is a seasonal upwelling system (where cooler SSTs only occur along the coast in particular seasons). Coastal upwelling systems, characterised by the upward flow of cool nutrient-rich waters from the deeper ocean to its surface, produce hotspots of biological activity and are crucial for ocean productivity. Our analysis relied on a method called canonical correlation analysis (CCA,) which identifies strongly linked variations between two spatio-temporal fields. The dominant modes of Atlantic SST variability associated with Eastern Pacific warm SST anomalies (also known as canonical El Niño events,) and Central Pacific warm SST anomalies (also known as Modoki El Niño events) are presented in panels e and d, respectively. Canonical El Niño events are strongly correlated with coastal cooling (indicative of stronger coastal upwelling) along the Western Sahara with a lag of 4 months, while Modoki El Niño events are weakly correlated with coastal warming (indicative of weaker coastal upwelling) along the Western Sahara at a lag of 2-3 months. It is possible that these teleconnections result from the comparatively better (poorer) alignment of East Atlantic trade winds with the coast of Western Sahara following Canonical (Modoki) El Niño events. The Pacific-North Atlantic teleconnection is known to modulate Atlantic trade winds through the Walker cell (atmospheric bridge) and atmospheric Kelvin waves.